Development of a demineralized and decellularized human epiphyseal bone scaffold for tissue engineering: A histological study. (December 2018) - Abedin, Elham; Lari, Roya; Mahdavi Shahri, Nasser; Fereidoni, Masoud
Graphical abstract: Highlights: Extracellular matrix (ECM) controls the cellular behaviors such as proliferation, migration, and differentiation. In this study, the decalcified and decellularized human epiphyseal bone matrix was used as a scaffold for a bone generation. The cells adhered and infiltrated into this natural bone scaffold. This scaffold had capability to induce bone mineralization, even in the standard culture medium. Abstract: Extracellular matrix (ECM) controls cellular behaviors such as proliferation, migration, and differentiation. The decellularized matrix of mammalian tissues has been used as a scaffold for the repair and reconstruction of tissue defects. In this study, for the first time demineralized and decellularized human epiphyseal bone matrix was used as a scaffold for a bone generation. Human epiphyseal bone was demineralized by hydrochloric acid and then decellularized by three methods of physical (slow freezing and snap freeze-thaw), enzymatic (trypsin 0.25%, 18 h) and chemical sodium dodecyl sulfate (SDS), )2.5%, 26 h). The scaffolds were cultured with rat adherent bone marrow cells (RABMC). Then, the histological studies were performed on days 7, 14, 21, and 28 of the culture to observe the distribution and morphology of cells. Bone formation was also investigated using Alizarin red staining. The results of this study indicated that RABMC migrated, proliferated and separated by forming lacuna in this three-dimensional bone scaffold. In addition, the Alizarin red staining indicated the calcium deposition on the scaffold in both bone differentiation and standard culture medium. The natural characteristic of the present bone scaffold, its cell adhesion features and capability to induce bone mineralization, even in the standard culture medium, provides a potentially optimal bone scaffold for bone tissue engineering.